2022
DOI: 10.3390/app12199906
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Cutting Blasting Efficiency of Hard Rock Tunnels under Different Charge Diameters

Abstract: Considering the low efficiency of cutting blasting in hard rock mine tunnels, a novel solution of increasing the charge diameter of the cutting holes was put forward. To investigate the influence of the charge diameter on the cutting blasting results, three different working conditions of Φ 32 mm, Φ 42 mm, and Φ 50 mm blasting holes combined with Φ 27 mm, Φ 35 mm, and Φ 45 mm cartridges, respectively, were taken as the investigation objects. At first, the theoretical destruction ranges of single cutting holes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Chen et al 23 carried out numerical analyses and model experiments of wedge cutting blasting under unidirectional pressure and described the adverse effects of unidirectional pressure on damage evolution, cavity volume, and block distribution. Using numerical simulation and full-scale tests, Cheng et al 24 and Gao et al 25 investigated the effect of the charge diameter on hard rock wedge cutting blasting and concluded that increasing the charge diameter could aggravate the breaking degree of the rock mass. In addition to the above studies that have focused on traditional wedge cutting patterns, several recent studies have introduced a hole-outer delay into deep-hole wedge cutting blasting.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 23 carried out numerical analyses and model experiments of wedge cutting blasting under unidirectional pressure and described the adverse effects of unidirectional pressure on damage evolution, cavity volume, and block distribution. Using numerical simulation and full-scale tests, Cheng et al 24 and Gao et al 25 investigated the effect of the charge diameter on hard rock wedge cutting blasting and concluded that increasing the charge diameter could aggravate the breaking degree of the rock mass. In addition to the above studies that have focused on traditional wedge cutting patterns, several recent studies have introduced a hole-outer delay into deep-hole wedge cutting blasting.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant progress has been made in the study of blasting mechanisms with the advancement of physical experiments and numerical simulation techniques [16][17] . Researchers have investigated the mechanisms of rock blasting and fragmentation, as well as the patterns of stress and fracture changes, under different charging structures [18][19] and detonation velocities [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%